APLIKASI UMPAN RAYAP BERBAHAN AKTIF HEXAFLUMURON PADA DOSIS BERBEDA DALAM PENGENDALIAN SERANGAN RAYAP DI PERKEBUNAN KELAPA SAWIT - Farah Diba; Marselinus TM Simatupang; Lukas Siahaan; . Nurhaida; M Idham; M Yuli Irianto; . Zulfadhli (Tengkawang : Jurnal Ilmu Kehutanan, 2017)
Subterranean termites Coptotermes curvignathus has found as pest in oil palm plantation. The research aimed to control the termites in oil palm plantation using Hexaflumuron bait with different dosage. Location of research was oil palm plantation at Purun village in Mempawah Regency. The study was conducted by a completely randomized design method. The research treatment was dose of Hexaflumuron termite bait, consisting of 30 gram and 60 gram. Three blocks was choosing as a sample treatment consists of block H 35, block H 38 and block H 39. Hexaflumuron bait has weight 30 gram. Treatment dose of 30 gram was conducted with lay down the bait of Hexaflumuron at the mud tunnel of termites in the trunk of oil palm. Treatment dose of 60 gram was conducted with lay down two bait of Hexaflumuron at the mud tunnel of termites in the trunk of oil palm in the different place. Then inspection of bait consumption was conducted every week. Data of bait consumption and termites elimination was collected. Results of the research showed that Hexaflumuron bait was consumed by termites up to 100%. The bait has attracted the termites to consume and non-repellent to termites. After four until seven week consumption the Hexaflumuron bait, termites eliminated from the oil palm. The result of variance analysis showed that there was no significance difference between the dose of 30 gram and 60 gram  on the termite consumption level. Hexaflumuron bait was effective for termites elimination in oil palm plantation within four until seven weeks and dose 30 gram was optimum for termites elimination.Keywords: Coptotermes curvignathus, hexaflumuron, oil palm, termites bait, termites control